SCHISANDRA CHINENSIS BAILL, A CHINESE MEDICINAL HERB, ALLEVIATES HIGH-FAT-DIET-INDUCING NON-ALCOHOLIC STEATOHEPATITIS IN RATS - Yao, Zheng; Liu, Xiao-Chen; Gu, Ying-Er (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The present study aims to explore whether Schisandra chinensis Baill, a Chinese, medicinal herb can alleviates high-fat-diet-inducing non-alcoholic steatohepatitis in rats. In the study, 24, male Wister rats with body weight between 180-220g, were included. The rats were randomly divided into four groups: model group, normal control group, rosiglitazone group, and Schisandra chinensis Baill group. The treatment lasted for 56, days. The high-fat diet used in the present study includes 25% lard, 2%, cholesterol 0.5%, sodium cholate, and 25%, Tween-80. The hepatic levels of superoxide dismutase (SOD), and malondialdehyde (MDA); the serum levels of total cholesterol (TC), and low-density lipoprotein cholesterol (LDLC), were detected. We found that the hepatic levels of SOD were significantly lower, and the serum levels of TC, LDLC as well as, the hepatic levels of MDA in model group were significantly higher than those of normal control group; rosiglitazone group and Schisandra chinensis Baill group (P<0.05), indicates that non-alcoholic steatohepatitis rats were successfully induced by high-fat diet. Schisandra chinensis Baill group presented a significant lower serum levels of LDLC, than rosiglitazone group (P<0.05); and the hepatic levels of SOD in Schisandra chinensis Baill group were significantly lower than rosiglitazone group (P<0.05). However, no significant difference existed between Schisandra chinensis Baill group, and rosiglitazone group on the hepatic levels of MDA and the serum levels of TC (P>0.05). It is then concluded that Schisandra chinensis Baill can significantly alleviate the non-alcoholic steatohepatitis of the rats induced by high-fat diet, and it may be used as a complementary therapy for rosiglitazone.